Conserved multiepitopes in Plasmodium falciparum STEVORs enable rational design of a fusion antigen vaccine construct with broad immunogenicity - Zhi-Shan Sun; Jing-Xian Yin; Han-Qing Zhao; Yin-shan Zhu; Shen-Bo Chen; Hai-Mo Shen; Bin Xu; Xiao-Nong Zhou; Tian-Yu Wang; Wan-Xuan Yang; Yi-Wen Duan; Jun-Hu Chen; et al. (Emerging Microbes and Infections)
There is no vaccine for severe malaria. STEVOR antigens on the surface of Plasmodium falciparum-infected red blood cells are implicated in severe malaria and are targeted by neutralizing antibodies, but their epitopes remain unknown. Using computational immunology, we identified highly immunogenic overlapping B- and T-cell epitopes (referred to as multiepitopes, 7–27 amino acids) in the semiconserved domain of four STEVORs linked with severe malaria and protective immunity. Structural analyses confirmed the conservation in homologous sequences across 138 clinical isolates (Togo and Brazil) and 342 global strains. Designed fused multiepitopes showed high IgG antibody reactivity in the sera of P. falciparum-infected individuals. The fused multiepitopes had no allergenicity/toxicity, and phenotyping via flow cytometry and immunological assays revealed the induction of CD4 + and CD8+ T-cell proliferation and IgG antibodies in BALB/c mice, respectively. On this basis, structure-guided design of a multiepitope fusion antigen (MEFA) vaccine construct achieved 97.15% global combined HLA coverage and elicited both cellular and humoral immunity in silico. Recombinant MEFA was stably expressed in Escherichia coli and recognized significantly more anti-STEVOR IgG antibodies in the sera of nonsevere malaria cases than in those of severe cases, underscoring its potential immunogenicity and association with milder disease. The STEVOR MEFA construct emerges as a promising severe malaria vaccine candidate, combining global HLA coverage, safety, and broad immunogenicity linked to milder clinical outcomes.